BATAS USIA PERKAWINAN DI NEGARA-NEGARA MUSLIM KONTEMPORER DALAM PERSPEKTIF MAQĀṢID AL-SYARĪ‘AH: STUDI KOMPARATIF DELAPAN NEGARA - Nurhilal Nazri arif; Akbarizan; Nur Cahaya (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2026)
Underage marriage remains a prevalent phenomenon in many Muslim-majority countries, despite the ratification of international conventions on child protection. This practice is often legitimized by religious and cultural factors, gender inequality, and weak law enforcement. This article aims to conduct a comparative study of legal regulations concerning the minimum age of marriage in eight contemporary Muslim countries: Indonesia, Egypt, Saudi Arabia, Morocco, Malaysia, Algeria, Turkey, and Iran. The study employs a normative-qualitative approach through the analysis of legal documents and public policies in each country. The findings reveal significant differences in legal approaches, ranging from conservative frameworks to more progressive reforms in family law. The article highlights the importance of harmonizing national legal systems with Islamic principles of child protection in order to reduce the practice of child marriage and to safeguard the fundamental rights of girls in the contemporary Muslim world. Keywords: child marriage, family law, minimum marriage age, Muslim countries, comparative study.